A phase II study of capecitabine and oxaliplatin combination chemotherapy in patients with inoperable adenocarcinoma of the gall bladder or biliary tract. (December 2016) - Graham, J.; Boyd, K.; Coxon, F.; Wall, L.; Eatock, M.; Maughan, T.; Highley, M.; Soulis, E.; Harden, S.; Bützberger-Zimmerli, P.; Evans, T.
Abstract Background Advanced biliary tract carcinomas are associated with a poor prognosis, and palliative chemotherapy has only modest benefit. This multi-centre phase II study was conducted to determine the efficacy of capecitabine in combination with oxaliplatin in patients with inoperable gall bladder or biliary tract cancer. Methods This was a Phase II, non-randomised, two-stage Simon design, multi-centre study. Ethics approval was sought and obtained by the North West MREC, and then locally by the West Glasgow Hospitals Research Ethics Committee. Eligible patients with inoperable locally advanced or metastatic adenocarcinoma of the gall bladder or biliary tract and with adequate performance status, haematologic, renal, and hepatic function were treated with capecitabine (1000 mg/m2 po, twice daily, days 1–14) and oxaliplatin (130 mg/m2 i.v., day 1) every 3 weeks for up to six cycles. The primary objective of the study was to determine the objective tumour response rates (complete and partial). The secondary objectives included assessment of toxicity, progression-free survival, and overall survival. Results Forty-three patients were recruited between July 2003 and December 2005. The regimen was well tolerated with no grade 3/4 neutropenia or thrombocytopenia. Grade 3/4 sensory neuropathy was observed in six patients. Two-thirds of patients received their chemotherapy without any dose delays. Overall response rate was 23.8 % (95 % CI 12.05–39.5 %). Stable disease was observed in a further 13 patients (31 %) and progressive disease observed in 12 (28.6 %) of patients. The median progression-free survival was 4.6 months (95 % CI 2.8–6.4 months; Fig. 1) and the median overall survival 7.9 months (95 % CI 5.3–10.4 months; Fig. 2).Fig. 1 Progression-free survival Fig. 2 Overall survival Conclusion Capecitabine combined with oxaliplatin has a lower disease control and shorter overall survival than the combination of cisplatin with gemcitabine which has subsequently become the standard of care in this disease. However, capecitabine in combination with oxaliplatin does have modest activity in this disease, and can be considered as an alternative treatment option for patients in whom cisplatin and/or gemcitabine are contra-indicated.